Facile Preparation of Peptides for Mass Spectrometry Analysis in Bottom‐Up Proteomics Workflows. Issue 3 (22nd March 2021) - Wojtkiewicz, Melinda; Berg Luecke, Linda; Kelly, Maia I.; Gundry, Rebekah L.
Abstract: Mass spectrometry (MS) is routinely used to identify, characterize, and quantify biological molecules. For protein analysis, MS‐based workflows can be broadly categorized as top‐down or bottom‐up, depending on whether the proteins are analyzed as intact molecules or first digested into peptides. This article outlines steps for preparing peptide samples for MS as part of a bottom‐up proteomics workflow, providing versatile methods suitable for discovery and targeted analyses in qualitative and quantitative workflows. Resulting samples contain peptides of suitable size for analysis by MS instrumentation generally available to modern research laboratories, including MS coupled to either liquid chromatography (LC) or matrix‐assisted laser desorption/ionization (MALDI) interfaces. This article incorporates recent developments in methodologies and consumables to facilitate sample preparation. The protocols are well‐suited to users without prior experience in proteomics and include methods for universally applicable suspension trap processing and for alternate in‐solution processing to accommodate a range of sample types. Cleanup, quantification, and fractionation procedures are also described. © 2021 The Authors. Basic Protocol : Preparation of high‐complexity peptide samples for mass spectrometry analysis using S‐Trap™ processing Alternate Protocol 1 : Preparation of low‐ to moderate‐complexity peptide samples for mass spectrometry analysis using in‐solution processing Alternate Protocol 2 : Detergent, polymer, and salt removal from peptide samples before mass spectrometry analysis using SP2 processing Support Protocol 1 : Protein quantification using Pierce 660 nm assay Support Protocol 2 : Peptide quantification using Pierce quantitative fluorometric peptide assay Support Protocol 3 : High‐pH fractionation of complex peptide samples